Intervensi Spiritualitas untuk Menurunkan Tingkat Kecemasan dan Depresi terhadap Pasien Kanker - Yanti, Ida; Nuraini, Tuti; Edison, Chiyar; Gayatri, Dewi (Journal of Telenursing (JOTING), 2024)
This study aims to determine the factors that influence the level of spirituality and the level of anxiety and depression in cancer patients. The method used was a systematic review of several databases, such as Scopus, Google Scholar, PubMed, ProQuest, and EBSCOHost, which were used in the search for relevant articles. The research results show that there are a total of 9 articles that have been analyzed, one of which is the complex condition of cancer-causing sufferers to face various clinical symptoms, both physical and psychological, and the spirituality needed by cancer patients to provide comfort. In this context, the need for aspects of spirituality cannot be ignored because it can give comfort and positively impact the health and healing of patients. Therefore, fulfilling spiritual needs is very important, apart from paying attention to other aspects of needs in individuals experiencing cancer. Conclusion: The spiritual interventions carried out are suitable for reducing levels of anxiety and depression in cancer patients, including dhikr therapy, reading books about religion, spiritual counseling, nursing care based on a support-based spiritual care model, religious-spiritual psychotherapy, and Al-based group spiritual interventions. -Quran and Islam. Keywords: Anxiety, Depression, Cancer, Spirituality